Deep crustal structure in the eastern Gulf of Mexico. Issue 9 (11th September 2014) - Christeson, G. L.; Van Avendonk, H. J. A.; Norton, I. O.; Snedden, J. W.; Eddy, D. R.; Karner, G. D.; Johnson, C. A.
Abstract We use air gun data recorded by ocean bottom seismometers to constrain the velocity structure along Gulf of Mexico Basin Opening Line 4, a profile extending from the northwestern Florida peninsula across the Florida Escarpment to the central Gulf of Mexico. Moderately thinned continental crust with a Moho depth of 32–33 km, average sediment thickness of 6 km, and an average crustal thickness of 27 km is interpreted on the northeast end of the profile offshore Florida. Thinned and intruded continental crust is identified over a horizontal distance of 225 km where the crustal layer thins from 25 km to 6–7 km; mean seismic velocities of the crust in this region increase from 6.55 km/s to 6.95 km/s from northeast to southwest and are evidence for increased magmatic input as rifting developed. Oceanic crust with an average thickness of 5.6–5.7 km is observed over a distance of 175 km on the southwest end of the profile, with an extinct spreading ridge with an axial valley morphology imaged on a coincident seismic reflection profile. Anomalously high upper oceanic crust velocities of 6.0–6.7 km/s are interpreted as massive basalt flows and could reflect increased temperatures during emplacement. Integrating well, seismic reflection and our seismic refraction data allow us to estimate a full‐spreading rate of 2.2 cm/yr for seafloor spreading along the profile; this indicates that oceanic crust was emplaced at a slow‐spreading center.